‘Home Visit' as a Learning Method for Early Children During the Covid-19 Pandemic - Hajeni, Hajeni (THUFULA, 2022)
This descriptive, quantitative, and qualitative research aims to describe early childhood learning methods during the COVID-19 pandemic in Palopo City. This study is motivated by several problems; the lack of parental involvement in accompanying children to study at home, economic factors, the internet network, and a lack of interest in children participating in learning so that early childhoodcannot develop optimally. Data was gathered through interviews and questionnaires administered via the media google form to 69 teachers and principals in Palopo City.Data analysis uses source triangulation with the stages of data collection, data reduction, data display, and conclusion. This study's results indicate that teachers still use children's worksheets (LKA) assignments for learning during the COVID-19 pandemic. This study's novelty is that teachers use a new approach, namely, the visit-home method. Even though there are still a few, who use the home visit method, the home visit method is considered beneficial because the learning carried out is more effective compared to online. Students understand learning material more quickly and are interested in participating in learning at home. Researchers hope this home visit method will not only be applied during a pandemic.